EDUCATION ON BAY LEAF DECOCTION ADMINISTRATION TO REDUCE HYPERTENSION - Paizal, M; Siti Romadoni (OJS Universitas Muhammadiyah Gresik, 2025)
Abstract: Hypertension is one of the major health problems in the community, especially in urban areas such as Palembang. The high prevalence of hypertension in RT 60, Kelurahan 16 Ulu, indicates the need for effective health interventions. This community service activity aims to increase public awareness about hypertension and provide alternative solutions through herbal therapy using bay leaf decoction. The methods used include surveys, health education, health checks, and hypertension exercise training. The results showed an increase in community knowledge about hypertension and how to deal with it, as well as active participation in hypertension exercise activities. This activity is expected to be a model of community-based health intervention to reduce the prevalence of hypertension in the community. Keywords: hypertension; Herbal therapies; Health education.